Virtual interviews: Less carbon, less bias? - Rajajee Selvam; Husein Moloo; Helen MacRae; Fahad Alam; Isabelle Raiche (Elsevier, 2022)
Introduction: While moving to a virtual fellowship selection process was mandated by the coronavirus pandemic, hesitancy remains when it comes to a complete transition away from in-person interviews. To help programs with their decision making, this project aimed to document the experience of program directors and applicants undergoing a virtual selection process as we enter a post-pandemic era. Materials and Methods: Applicants and program directors involved in the 2020 Canadian Colorectal Fellowship Match were recruited to participate in this qualitative study via email. All programs carried out their selection process as per their protocol. Structured phone interviews were completed. The perspectives of applicants and program directors were extracted using directed content analysis. Results: All 6 program directors and 5 of 10 applicants participated. Main goals of the interview for both applicants and program directors were to share/gather information about the program and assess the fit between applicants and programs. Benefits of virtual interviews included reduction in the financial, opportunity, and environmental costs. However, it was noted that assessment of fit and interpretation of body language was more challenging. Conclusion: Virtual interviewing is a feasible alternative to face-to-face interviews for Canadian Colorectal Fellowship programs, with clear benefits from an environmental impact perspective. Further research on how to assess fit fairly through a virtual platform may be useful in developing a selection process that is just, while appreciating our role as healthcare leaders in the climate crisis.